Evidências de validade do teste de Pfister informatizado com crianças - Guimarães, Ingrid Gomes (2024)
The Pfister Colored Pyramids Test assesses personality dynamics and cognitive functioning by filling in pyramid schemes with colored squares. The computerized version of this test was developed in 2021, but its future use in psychological assessment processes requires investigation of its validity evidence. Based on the assumption that there are emotional consequences in the life cycle of children who have experienced sexual abuse and that psychological assessment can provide data to support psychological interventions to be carried out with the victims, the objective was to seek evidence of the validity of the computerized version of Pfister's Colored Pyramids test for use with children. The total sample consisted of 91 participants aged between 6 and 10 years (M = 8.52; SD = 1.36), 37 with a history of reported sexual abuse and 54 without. The computerized Pfister Test (TPC-i) and the Personality Traits Scale for Children (PTSC) were administered, as well as a Sociodemographic Questionnaire, whose data regarding the abuse situation was filled in by researching the medical records. In the data analysis, descriptive statistics and frequency analyses were carried out to characterize the sample, and Cohen's Kappa coefficient was used to investigate the reliability of the computerized Pfister Test database. To find evidence of convergent validity evidence for the computerized Pfister with the PTSC, Spearman's correlation and point-biserial analyses were conducted. There were negative correlations between the trait extroversion and emotional adaptation (Az1); psychoticism and anxiety with signs of controlling emotions (Az3 and violet); neuroticism and restraining impulsiveness (Vm3), as well as stability and maturity (upward placement). There were also positive correlations between psychoticism and the possibility of irritability (Am2); and neuroticism with anxiety (Vi1) and insecurity (downward placement). To find evidence of concurrent validity, normality tests were conducted and then children aged between 6 and 8 and 9 and 11 were compared using the Mann-Whitney U-test. Children aged between 6 and 8 had more signs of impulsivity (Vm4), excitability (La1), energy (Ma2 and brown color), as well as less ability to regulate emotions (pure mat), immaturity (downward placement) and disorganization (spatial placement). Using the same analyses and Fisher's Exact Test, children with and without a history of reported sexual abuse were compared. Children with a history of abuse had more signs of social withdrawal (lower mean Vd1 score) and lower emotional adaptation (lower mean Az1 score, blue color and cold syndrome). Point-biserial correlation and the Chi-square test were used to find evidence of convergent validity between characteristics of the abuse situation and the TPC-i. A relationship was observed between the fact that the aggressor was intrafamilial, had experienced other forms of violence and had more signs of anxiety. Finally, binary logistic regression was used to find evidence of predictive validity for the TPC-i, and only the anxiety indicator (Vi1) contributed to increasing the likelihood of identifying participants with a history of intrafamilial sexual abuse, as well as those who had experienced violence other than sexual abuse. Through these results, it was possible to identify evidence of concurrent and convergent validity for the TPC-i, and it is understood that the research contributed to increasing the psychometric qualities and studies on the use of this test with children.